1996
DOI: 10.1164/ajrccm.154.6.8970362
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between chronic dyspnea and expiratory flow limitation in patients with chronic obstructive pulmonary disease.

Abstract: The purpose of this study was to assess whether expiratory flow limitation (FL), as measured by applying negative pressure at the mouth during tidal expiration, is a better predictor of dyspnea than routine spirometry measurements. The study population consisted of 117 ambulatory patients with COPD. Dyspnea was assessed according to the ATS-DLD respiratory Questionnaire. Expiratory flow limitation was measured in supine and sitting positions, and expressed as a percentage of the expired control tidal volume af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
227
4
21

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 263 publications
(265 citation statements)
references
References 26 publications
13
227
4
21
Order By: Relevance
“…In addition, it was found that 1) in all non-FL patients IC was within normal limits and in the majority of FL subjects the IC was below normal limits; and 2) in all FL subjects V'O 2 ,max was decreased, whereas in 35% of the non-FL patients V'O 2 ,max was within normal limits. In line with ELTAYARA et al [7], a high incidence of FL was found (56% versus 59%, respectively), indicating that FL is a frequent but unrecognized abnormality in these patients. The presented data also confirmed the findings of KOLOURIS et al [8] that a reduced IC is a good marker of FL, as it reflects dynamic hyperinflation (DH).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In addition, it was found that 1) in all non-FL patients IC was within normal limits and in the majority of FL subjects the IC was below normal limits; and 2) in all FL subjects V'O 2 ,max was decreased, whereas in 35% of the non-FL patients V'O 2 ,max was within normal limits. In line with ELTAYARA et al [7], a high incidence of FL was found (56% versus 59%, respectively), indicating that FL is a frequent but unrecognized abnormality in these patients. The presented data also confirmed the findings of KOLOURIS et al [8] that a reduced IC is a good marker of FL, as it reflects dynamic hyperinflation (DH).…”
Section: Discussionsupporting
confidence: 84%
“…1). The FL portion of the tidal expiration was expressed as a percentage of the control VT (FL, %VT) [7]. The latter is presented as average of the five NEP tests.…”
Section: Procedures and Data Analysismentioning
confidence: 99%
See 3 more Smart Citations